Correlation between Dietary Inflammatory Index and Lipid Profile on Female Workers - Sarbini, Dwi; Febrian, Novi Gita Noer; Puryaningtias, Rini Dwi (Prosiding University Research Colloquium, 2025)
Dyslipidemia is associated with metabolic syndrome. The increasing of blood cholesterol levels, low-density lipoprotein levels, triglyceride levels, and decreasing of high-density lipoprotein levels can be caused by a high intake of a pro-inflammatory diet. This study aims to determine the correlation between the dietary inflammatory index and lipid profiles (blood cholesterol levels, low-density lipoproteins, triglycerides, and high-density lipoproteins) in female workers at PT Iskandar Indah Printing Textile. This study is an observational study with a cross-sectional approach. The samples are female workers aged 26-45 years who taken by proportional random sampling of 34 female workers who meet the inclusion and exclusion criteria. Inflammatory dietary intake was analyzed by a semi-quantitative food frequency questionnaire, and lipid profiles were measured using by spectrophotometer methods. The statistical test carried out is using by Rank Spearman Correlation (p<0,05). We found almost of samples who has moderate category of dietary inflammatory index intake (41.2%), HDL levels nearby optimal or normal (94.1%) and high triglyceride levels (44.7%). We also found 11.8% of samples on high cholesterol levels and 17.6%) on high LDL level. There were no significant correlation between dietary inflammatory index and lipid profiles among female workers at PT Iskandar Indah Printing Textile (p<0,05.).